Selective Complexometric Determination of Copper in Alloys using L-Cysteine - Narayana, B.; Gajendragad, M.R. (Asian Journal of Chemistry, 2010)
An accurate, selective and rapid complexo-titrimetric method is described for the determination of copper in alloys. The method is based on the selective complexing ability of L-cysteine with copper. Copper in the alloy solution, initially complexed by the addition of EDTA solution and the excess EDTA is titrated against lead nitrate solution (pH 5.0–6.0) using hexamine and xylenol orange. A known excess of Lcysteine in water is then added to release the EDT A from the Cu-EDT A complex. This is subsequently titrated against lead nitrate to the sharp end point as before. The amount of EDTA replaced from the complex is thus equivalent to the amount of copper in the alloy solution.